Formulation of Scientific Concepts as a Component of the Research Competence of Future Teachers - T. F. Orekhova; T. G. Neretina; E. N. Kondrashova (Высшее образование в России)
The article presents the authors’ method of teaching undergraduate and Master’s degree students majoring in education to formulate scientific concepts including the key concepts that constitute the theoretical basis of any pedagogical research. We regard this skill as one of the components of the research competence of a modern teacher. In accordance with his labor functions, he (she) has to lead the research and project activities of students in the system of primary, basic and secondary general education. The article reveals the content of research competence which includes two groups of research skills: work with literary sources and actual work with text of a research. The authors consider three types of tasks for the formulation of scientific concepts of different levels of complexity, describe an algorithm for performing by students tasks of each type. In addition, the article reveals the pedagogical significance of teacher’s ability to formulate scientific concepts and describes the positive results of mastering this skill by undergraduates and Master’s degree students in education.